Ang Pagdadalaga ni Maximo Oliveros The Blossoming of Maximo Oliveros - Lee, Raymond; Yamamoto, Michiko 1936-; Solito, Auraeus; Lopez, Nathan; Cruz, Soliman; Valentin, JR; Sese, Neil Ryan; Medina, Ping; Pascua, Bodjie (Unico Entertainment, 2005)
Maxi, 12-year old gay lad, lives with his father and two brothers who steals for a living. On the verge of puberty, he develops a crush on Victor, an honest and handsome policeman. Victor encourages Maxi to go back to school and hope for a better life. But their friendship ended, when Victor's crime investigation lead him to Maxi's family.